Professionalism of AqidahAkhlak Teachers in the Utilization of Digital-Based Learning Media - Mohammad Saat Ibnu Waqfin; Samirin samirin (SCHOOLAR: Social and Literature Study in Education, 2022)
Teacher professionalism is a necessity that cannot be postponed anymore. Based on field supervision and document data (Teacher Competency Test), it is predicted that several causes of low student achievement include: 1) most teachers still use the teacher centered learning approach with lecture dominance and less variation in learning models; 2) the level of teacher professionalism is still not as expected. For this reason, teachers must be demanded to be more professional in using media and methods in the learning process, while the media itself is a tool that has the function of conveying messages, especially in learning aqidah morals. This study aims to analyze how professional Aqidah Akhlak teachers are and the obstacles they face in utilizing digital-based learning media. This research uses a descriptive qualitative approach. The results of this study found that the professionalism of teachers in using digital-based media was sufficient because it was supported by teacher training in using digital-based learning media, one of which was Google E-learning. As for some of the obstacles faced by the teacher, including the age factor which resulted in delays in studying the media and some students who worked during class hours and the data packages that were owned by students so that it slightly hampered learning